Αποξηραμένα στέμφυλα σιτηρού στην παραγωγή γάλακτος - Ζήνωνος, Ανδρέας (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The purpose of this dissertation was to investigate the effect of dried and wet distiller’s grains on milk production through bibliographic reviews and reports. Dried and Wet Distillers Grain with Soluble are bioethanol by-products that are produced from the extraction of starch contained in grains such as maize and wheat. According to research, DDGS is a very good source due of high protein and adequate energy content for dairy animals as shown by their use worldwide. In conclusion, milk production is increased when in the dairy cow ration has between 20% and 30% DDGS, while in sheep diet the DDGS can be included up to 30% in order to have the desired results. In DDGS-enhanced studies (30%) it was observed to have a negative effect on the health of animals as well as on milk production. The administration of WDGS to dairy cows' feeds of up to 20% according to the literature increases in the production of milk by DDGS. Furthermore, the administration of bioethanol by-products to the percentages mentioned has a positive effect on the quality characteristics of milk such as fat, protein and lactose. According to the literature, regarding the fat quality and the fatty acid profile with the addition of DDGS and WDGS, the increase in polyunsaturated and monounsaturated fatty acids and a reduction of saturated fatty acids are observed. The use of DDGS in dairy cows reared in hot climates was also assessed and milk production increased by 2kg-4kg / day when 7.5% DDGS and 15% DDGS were included in the diet respectively. Finally, a limiting factor in the use of these by-products as a result of fungi infection is reported in the literature. DDGS infected by fungi can occur from field or subsequent storage of the by-product resulting in the production of mycotoxins that will have a direct impact on the health of animal and consumer. From this bibliographic review, it is concluded that bioethanol by-products can be used in animal feed rations in Cyprus for the production of milk, which their use to date is limited. Their use could replace other proteinaceous feeds such as soybean, since the price and other precautions regarding the existence of mycotoxins in DDGS products are being applied.
Keywords: Wet Distillers Grain; Dried Distillers Grain; Milk production; Γαλακτοπαραγωγή; WDGS; DDGS